Active matter therapeutics. (April 2020) - Ghosh, Arijit; Xu, Weinan; Gupta, Neha; Gracias, David H.
Graphical abstract: Highlights: Active particles can significantly augment the capabilities of modern drug delivery. Active particles can harness energy from the environment or external fields and show enhanced transport properties. Active particles can exert pressure of a magnitude similar to the interstitial fluid pressure in solid tumors. Recent advances suggest that active particles can degrade clots in blood vessels by mechanical rubbing. Abstract: Nanotherapies based on micelles, liposomes, polymersomes, nanocapsules, magnetic nanoparticles, and noble metal nanoparticles have been at the forefront of drug delivery in the past few decades. Some of these nanopharmaceuticals have been commercially applied to treat a wide range of diseases, from dry eye syndrome to cancer. However, the majority involve particles that are passive, meaning that they do not change shape, and they lack motility; the static features can limit their therapeutic efficacy. In this review, we take a critical look at an emerging field that seeks to utilize active matter for therapeutics. In this context, active matter can be broadly referred to as micro or nanosized constructs that energetically react with their environment or external fields and translate, rotate, vibrate or change shape. Essentially, the recent literature suggests that such particles could significantly augment present-day drug delivery, by enhancing transport and increasing permeability across anatomical barriers by transporting drugs within solid tumor microenvironments or disrupting cardiovascular plaque. We discuss examples of such particles and link the transport and permeability properties of active matter to potential therapeutic applications in the context of two major diseases, namely cancer and heart disease. We also discuss potential challenges, opportunities, and translational hurdles.